GDP steady-state multipliers under monopolistic competition revisited - Costa, Luís F. (2007)
New Keynesian general-equilibrium static models showed the fiscal multiplier is an increasing function of the degree of monopoly. Here, I develop a simple intertemporal model allowing us to study the steady-state role of optimal capital stock (and depreciation) in the fiscal policy transmission mechanism. The GDP multiplier may be locally decreasing in the degree of monopoly when the number of firms is fixed, but results depend strongly on the set of parameter values chosen. Using a net-output definition or allowing for free entry leads to unambiguous dominance of the long-run monopolistic multiplier over the Walrasian one.